Etude des annélides de la lagune ElMellah, El-Taref, L’Algérie. - Merabti Safa; Meniai Ilham (My University, 2018)
In general, the study of the demographic structure (density) and biomass of annelids of the Mellah during four months (January, February, July, August) through six stations spread over two sectors opposes the lagoon (North, South), showed that the Mellah contains abundances (1581.66 ± 0.28) ind.m-2) and biomasses (1.70 gm-2) weak in comparison with the majority of Mediterranean lagoons. Moreover, it should be remembered that the annelids count (10) are dominated by three speciesCapitellacapitata,NainereislaevigataandMicronereisvariegata, distributed over two different sectors according to their resistance and their biological need which plays a major role in their distribution across the months. ------------------------------------------------------------------------------------------- بشكل عام ، فإن دراسة التركيبة السكانية (الكثافة) والكتلة الحيوية لأجناس الملاح خلال أربعة أشهر (يناير ، فبراير ، يوليو ، أغسطس) من خلال ست محطات موزعة على قطاعين تعارض البحيرة (الشمال والجنوب) ، أظهر أن الملاح يحتوي على وفرة (1581.66 ± 0.28) indm-2) والكتل الحيوية (1.70 جم -2) ضعيفة بالمقارنة مع غالبية البحيرات البحر الأبيض المتوسط. من جهة أخرى،يجب أن نتذكر أن أعداد الأجناس (10) هي التي تهيمن عليها ثلاثة أنواعمنCapitellacapitata،Nainereislaevigata و Micronereisvariegata، موزعة على قطاعين مختلفين وفقا لمقاومتها وحاجتها البيولوجية التي تلعب دورا رئيسيا في توزيعها عبر الأشهر. --------------------------------------------------------------------------------------------- D’une manière générale, L’étude de la structure démographique (densité) et de la biomasse des annélides du Mellah au cours de quatre mois (janvier, février, juillet, août) à travers six stations réparties sur deux secteurs oppose de la lagune (Nord, Sud), a montré que le Mellah renferme des abondances (1581.66 ±0.28) ind.m-2) et des biomasses (1.70 g.m-2) faibles en comparaison avec la majorité des lagunes méditerranéennes. Par ailleurs, il faut rappeler que les annélides recenser (10) sont dominer par trois espèces Capitellacapitata,Nainereislaevigataet Micronereisvariegata , repartie sur deux diffèrent secteurs selon leur résistances et leur besoin biologique qui joue un rôle majeur dans leur distribution à travers les mois.